CdSe Quantum Dots and N719‐Dye Decorated Hierarchical TiO2 Nanorods for the Construction of Efficient Co‐Sensitized Solar Cells. Issue 12 (16th July 2015) - Subramaniam, Mohan Raj; Kumaresan, Duraisamy
Abstract Three‐dimensional hierarchical TiO2 nanorods (HTNs) decorated with the N719 dye and 3‐mercaptopropionic or oleic acid capped CdSe quantum dots (QDs) in photoanodes for the construction of TiO2 nanorod‐based efficient co‐sensitized solar cells are reported. These HTN co‐sensitized solar cells showed a maximum power‐conversion efficiency of 3.93 %, and a higher open‐circuit voltage and fill factor for the photoanode with 3‐mercaptopropionic acid capped CdSe QDs due to the strong electronic interactions between CdSe QDs, N719 dye and HTNs, and the superior light‐harvesting features of the HTNs. An electrochemical impedance analysis indicated that the superior charge‐collection efficiency and electron diffusion length of the CdSe QD‐coated HTNs improved the photovoltaic performance of these HTN co‐sensitized solar cells.